Insights on the role of TLR-4 in neuroinflammation: a hint on COVID-19 relationship - Salma A. Elshafey; Dalia El-Khouly; Esther T. Menze; Mariane G. Tadros (Archives of Pharmaceutical Sciences Ain Shams University, 2023)
Neuroinflammation plays a crucial role in cognitive decline and neurodegenerative diseases, such as Alzheimer's. Within the central nervous system, microglia express Toll-like receptor 4 (TLR-4) abundantly, which prompts the secretion of proinflammatory cytokines like TNF-α, PGE2, IL-1β, and NO that are considered essential components of neuroinflammation. The emergence of neurological complications in COVID-19 patients has spurred investigations into TLR-4's potential involvement. Particularly intriguing is its contribution to the cytokine storms triggered by SARS-CoV-2 and SARS-CoV-1 infections. This comprehensive review investigates the TLR-4-induced neuroinflammation, focusing on its potential connection to cognitive decline and neurological symptoms triggered by COVID-19. By unraveling the intricate mechanisms by which TLR-4 mediates neuroinflammation, this review aims to shed light on its possible role in the context of COVID-19. Understanding the implications of TLR-4 activation could pave the way for targeted interventions to alleviate the cognitive and neurological impacts of COVID-19. As the world seeks to comprehend the far-reaching effects of the pandemic, grasping the nuances of TLR-4-associated neuroinflammation stands as a crucial step in addressing the challenges posed by cognitive decline and neurological manifestations in COVID-19 patients.